2015
DOI: 10.1016/j.memsci.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Application of electrodialysis for the treatment of almond industry wastewater

Abstract: In this work, electrodialysis has been proved to be a suitable technique for decreasing the conductivity of a real wastewater from an almond industry, which has been previously treated by electrocoagulation (EC) and electrooxidation (EO). A seven-cell electrodialyzer, with total active membrane area of 1400 cm 2 , was employed and several parameters, as the limiting current density, were determined. A method for measuring voltage across the membranes was developed, in order to control membrane fouling. The met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…PO4-P and NH4-N) from effluents [8,9,22,23,25] and desalination [9,15,26,27]. ED can also be implemented for the treatment of industrial wastewater [17,28] such as reducing electrical conductivity from almond industry [29], chloride removal from wet flue gas desulfurization wastewater [28], or removal of harmful ions such as F -, NO3 -, CLand Brand heavy metals such as pb 2+ , Ni 2+ , Cu 2+ , Cr 3+ , Mn 2+ , Fe 3+ , etc. [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…PO4-P and NH4-N) from effluents [8,9,22,23,25] and desalination [9,15,26,27]. ED can also be implemented for the treatment of industrial wastewater [17,28] such as reducing electrical conductivity from almond industry [29], chloride removal from wet flue gas desulfurization wastewater [28], or removal of harmful ions such as F -, NO3 -, CLand Brand heavy metals such as pb 2+ , Ni 2+ , Cu 2+ , Cr 3+ , Mn 2+ , Fe 3+ , etc. [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…After ED treatment, the diluate contained close to zero nickel ions [36]. Other authors also report high removal efficiency of heavy metals with ED treatment [37 -41] and for desalination [41,42] The ED process depends on several parameters, e.g., applied voltage or current, conductivity, pH, and concentration of the electrolyte [53]. The performance and lifetime of ED modules are affected by scaling and fouling phenomena of IEMs due to low solubility of some salts, organic substances, and colloidal particles of the influent [17].…”
Section: Electrodialysismentioning
confidence: 90%
“…After ED treatment, the diluate contained close to zero nickel ions . Other authors also report high removal efficiency of heavy metals with ED treatment and for desalination , . In Tab.…”
Section: Removal Of Inorganic Compoundsmentioning
confidence: 99%
“…The coagulant performed a similar function as the electrodes, neutralizing the charge of the particulates, thus allowed them to collect and settle at the bottom of the tank. In addition, electrocoagulation-flotation is talented of reducing waste production, time and electrical energy consumption for wastewater [7] [8] [9] while [10] and [11] enhanced electrocoagulation device for treating various types of industrial wastewater and observed how electrocoagulation-flotation(ECF) reactor can be effective, according to wastewater type, pH, current density and type of metal electrodes (aluminum, steel). Among all the various technologies available, electrolysis is one of the best.…”
Section: Introductionmentioning
confidence: 99%